The duties of a resulting trustee. Issue 8 (4th August 2020) - Collings, Matthew
Abstract: The precise duties surrounding express trusts have caused issues enough (as we explore in this journal)—but what of the duties of resulting trustees? They have been considered in the authorities, and have been the subject of academic commentary, but have nevertheless remained somewhat opaque. A recent judgment in the Court of Appeal in Singapore (its highest court) has thoroughly traversed the principal English and Commonwealth authorities and collated the academic articles. It provides a comprehensive and valuable insight into the duties of resulting trustees.